Tato sebagai Metode Identifikasi Korban Meninggal Tanpa Identitas - Niufti Ayu Dewi Mahila Mahila (Indonesian Journal of Legal and Forensic Sciences, 2024)
The identification of individuals is a critically important aspect of the forensic examination process, as errorsin the identification process can have fatal consequences in the legal proceedings. The identification of a living patientcan be carried out through various methods, including fingerprint identification, visual recognition, documentation,accessories, dental records, serological examinations, and biomolecular analysis. Presented is a case study of a maleindividual who died as a result of a motor vehicle accident involving a bus, which resulted in head and chest trauma,leading to the victim's immediate demise at the scene. No identifying marks were found on the victim, but the victimhad a tattoo on the left chest. Identification and external examinations were conducted by a team of doctors andINAFIS personnel, synchronized with the information provided by the victim's family. Subsequently, an analysis wasperformed, correlating with a review of the literature based on scientific publications. The final result was thesuccessful identification of the deceased individual, thus concluding that tattoos can be used as one of the methods ofidentification for individuals or unidentified bodies, supported by other methods such as family data and other uniqueindividual characteristics. However, the use of tattoos needs to be handled with caution due to the risk of infection,allergies, or the transmission of infections through poorly executed and unclean tattoo procedures.